2013
DOI: 10.1002/asna.201211871
|View full text |Cite
|
Sign up to set email alerts
|

Metal jumps across sloshing cold fronts: The case of A 496

Abstract: Cold-fronts in cool-core clusters are thought to be induced by minor mergers and to develop through a sloshing mechanism. While temperature and surface-brightness jumps have been detected and measured in many systems, a detailed characterization of the metal abundance across the discontinuity is only available for a handful of objects. Within the sloshing scenario, we expect the central cool and metal rich gas to be displaced outwards into lower abundance regions, thus generating a metal discontinuity across t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…We have shown that in relaxed (e.g. Ghizzardi et al 2013) and intermediate systems ) entropy and metallicity tend to anti-correlate, i.e. regions of lower entropy are more metal-rich.…”
Section: Abundance Bias In the Outskirtsmentioning
confidence: 88%
See 1 more Smart Citation
“…We have shown that in relaxed (e.g. Ghizzardi et al 2013) and intermediate systems ) entropy and metallicity tend to anti-correlate, i.e. regions of lower entropy are more metal-rich.…”
Section: Abundance Bias In the Outskirtsmentioning
confidence: 88%
“…For example some have attempted to use metals as tracers of gas motions in the ICM (e.g. Ghizzardi et al 2013;. A few (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Previously analysed metallicity profiles, based on deprojected (Sanders et al 2005), but more often projected (e.g., Ghizzardi et al 2007;Rossetti et al 2007;Simionescu et al 2010;Fabian et al 2011;Russell et al 2012;Ghizzardi et al 2013;Walker et al 2017), data, suggested a sharp drop in Z across CFs, qZ ≡ Zi/Zo > 1. The only metallicity profiles that were, as far as we know, previously deprojected across a CF (Sanders et al 2005(Sanders et al , 2016, suggested such a drop at only marginal, 2σ confidence levels.…”
Section: Metallicity Dropsmentioning
confidence: 99%
“…The oscillations occur in the plane of the orbit of the infalling perturber. When this plane is close to the plane of the sky, the sloshing produces a characteristic spiral pat- tern in surface brightness residuals, temperature and abundances, as cool, enriched gas is left behind by the motion of the core and warmer gas is drawn inwards (e.g., Roediger et al 2012;Gastaldello et al 2013;Ghizzardi et al 2013;Su et al 2017). However, when the plane is orthogonal to the plane of the sky, our line of sight passes through the spiral, producing alternating positive and negative arc-shaped residuals to either side of the core as in, e.g., the galaxy group NGC 5044 (O'Sullivan et al 2014) or galaxy clusters such as Abell 1795 (Markevitch et al 2001;Ehlert et al 2015), Abell 2219 (Canning et al 2017) or Abell 1664 (Calzadilla et al 2019).…”
Section: Sloshingmentioning
confidence: 99%